Casual Microtasking: Embedding Microtasks in Facebook - Hahn, Nathan; Iqbal, Shamsi; Teevan, Jaime (CHI 2019, 2019)
Microtasks enable people with limited time and context to contribute to a larger task. In this paper we explore casual microtasking, where microtasks are embedded into other primary activities so that they are available to be completed when convenient. We present a casual microtasking experience that inserts writing microtasks from an existing microwriting tool into the user’s Facebook feed. From a two week deployment of the system with nine people, we observe that casual microtasking enabled participants to get things done during their breaks, and that they tended to do so only after first engaging with Facebook’s social content. Participants were most likely to complete the writing microtasks during periods of the day associated with low focus, and would occasionally use them as a springboard to open the original document in Word. These findings suggest casual microtasking can help people leverage spare micromoments to achieve meaningful micro-goals, and even encourage them to return to work.